Traditional Medicine Practices Using Arabic Symbols - Irawati, Retno Purnama; Arifin, Akbar Syamsul; Kuswardono, Singgih; Miftahuddin, Ahmad; Siminto, Siminto (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This research aimed to explore the forms and characteristics of Arabic written symbols used in traditional medicine. Traditional medicine is in demand by the public, because of the perceived high cure rate and the failure of modern treatment that patients have undergone after undergoing medical treatment. Traditional medicine is more convincing than medical treatment. There has not been much research regarding the characteristics and methods of traditional medicine using Arabic symbols/writing. Arabic symbols or writing have been researched more in terms of meaning and ritual. Hence, this research utilized data source triangulation and technical triangulation. This qualitative research adopted a phenomenological approach. The research subjects were traditional medicine practitioners who used Arabic symbols/writing in their treatments and patients who had used traditional medicine. Determining the subjects of this research was carried out using a purposive sampling technique. The research results showed that prayers originating from the Qur'an and rajah with Arabic letter symbols were the therapist's mainstay medicine for treating patients. The use of prayers and rajahs with Arabic letter symbols varied from one therapist to another. Rajah in traditional medicine was used to treat various kinds of patient complaints. The rajah writing came from the books of Shams al Ma'arif al Kubra and Al Mujarrabat. Rajah came from verses from the Qur'an which were rewritten in the book of medicine. Proper interpretation and use of the Qur'an could provide effective improvements to a person's weak mental and psychological condition.